The Eliade guide to world religions - Eliade, Mircea, 1907-1986 (Harper San Francisco, 1991)
This is a one-volume distillation of the 16-volume "Macmillan Encyclopaedia of Religion". The history of 33 religions and information concerning religious events, notions and personalities are listed. The dictionary is arranged in two parts, with both summaries and definition of terms.